Delegation in long-term relationships - Miriam Schütte; Philipp C. Wichardt (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
This paper considers the e effcts of a two-period interaction on the decision of a principal to delegate authority to a potentially biased but better informed agent. Compared to the (repeated) one-period case, the agent's first period actions may also signal his type which in turn impacts wages in Period 2. As a result, biased agents have an incentive not to follow their own preferences in Period 1, thereby inducing the principal to delegate more often. Moreover, we find that, depending on the players' relative utilities and the wage schedule, long term relationships will increase aggregate welfare. Finally, to empirically support our findings, we analyse data from the German Socio-Economic Panel (SOEP) which show that temporary workers indeed experience less autonomy in their decisions.
Keywords: C72; C73; D82; D86; L22; M54; 330; delegation; signalling; reputation